2010
DOI: 10.1016/j.bcp.2010.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of diclofenac in leukocytes through the targeting of Kv1.3 voltage-dependent potassium channels

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. A c c e p t e d M a n u s c r i p t 1 2 3 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
80
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 40 publications
7
80
0
Order By: Relevance
“…We adopted two different cell culture sorting patterns for the assay of mRNA levels (Fig. 4, A and C The effect of ADWX-1 on channel expression is similar to that reported for diclofenac, a nonsteroidal anti-inflammatory drug that inhibits Kv1.3 expression in activated T lymphocytes (40). However, diclofenac is not a specific Kv1.3 channel blocker, and the mechanism involved in its inhibition of Kv1.3 expression is unknown.…”
Section: Ccr7mentioning
confidence: 75%
“…We adopted two different cell culture sorting patterns for the assay of mRNA levels (Fig. 4, A and C The effect of ADWX-1 on channel expression is similar to that reported for diclofenac, a nonsteroidal anti-inflammatory drug that inhibits Kv1.3 expression in activated T lymphocytes (40). However, diclofenac is not a specific Kv1.3 channel blocker, and the mechanism involved in its inhibition of Kv1.3 expression is unknown.…”
Section: Ccr7mentioning
confidence: 75%
“…In addition to acute inhibition of functional Kv1.3 channels, Kv1.3 blockers have been shown to produce anti-inflammatory and immunomodulatory effects through chronic reduction of the channel expression [11,12,14,27]. Before analysis, we confirmed that treatment with 10, 30 or 100 μmol/L Acacetin for up to 24 h did not result in any cytotoxicity in Jurkat cells, as assessed using both a CCK-8 kit and trypan blue dye (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since NSAIDs inhibit the production of cytokines from lymphocytes [2,3,4], they are also used as immunomodulatory drugs [5,6]. However, in some situations, such as in food-dependent exercise-induced anaphylaxis (FDEIA) [7,8], salicylate and its acetyl derivative, aspirin, can stimulate chemokine release from mast cells, triggering adverse immunological reactions [9,10].…”
Section: Introductionmentioning
confidence: 99%